Thin-Film Aspects of Superconducting Nickelates - Bernardini, F.; Iglesias, L.; Bibes, M.; Cano, A. (Frontiers in Physics, 2022)
The discovery of superconductivity in infinite-layer nickelates has attracted much attention due to their association to the high-T_c cuprates. Cuprate superconductivity was first demonstrated in bulk samples and subsequently in thin films. In the nickelates, however, the situation has been reversed: although surging as a bulk phenomenon, nickelate superconductivity has only been reported in thin films so far. At the same time, the specifics of infinite-layer nickelates yield distinct interface and surface effects that determine their bulk vs thin-film behavior. In this paper, we provide an overview on these important aspects.